Utilization of Solar Power Plants to Drive Organic Waste Shredding and Grinding Machines - Rahmad Samosir; Bambang Widodo; Budiarto Budiarto; Manogari Sianturi; Medyawanti Pane (Universitas Sultan Ageng Tirtayasa, 2024)
Solar power plants continues to experience good development and even PLTS can be used to overcome environmental problems, so this research aims to utilize renewable energy as a driving force for waste processing machines by designing organic waste chopping and grinding equipment. The specified motor power is 2 HP or 1.5 kW with 275 rpm, so the number of panels required is 12 pieces which are converted into AC from DC by the inverter. Based on power and rotation, the torque calculation results obtained are 2760 kg cm, the shaft diameter is 18.86 mm, the belt type is type A with a top belt width of 12.5 mm and a thickness of 8 mm, and transverse pegs with a width of 8 mm, a thickness of 7 mm. and 40 mm long based on ISO 2292 (according to pulley hub thickness). Based on the calculations and transmission design, a waste processing tool was built and then tested. From the tests, it was found that the power produced by PLTS was 1.5583 kW at 2239 Lux light to chop up 2 kg of organic waste.